Therapeutic efficacy of ozone insufflations in alleviating endometritis in cows - Patra, Bijay Kumar; Nath, Indramani; Nayak, Kuresh Kumar; Mishra, Rajshree; Mishra, Chinmay; Biswal, Shuvranshu Shek har; Sahoo, Anjan Kumar; Parida, Sunil Manohar (The Indian Journal of Animal Reproduction, 2023)
The present investigation was carried out to study the effect of intrauterine ozone insufflation alone or in combination with cephalexin in treating the postpartum clinical endometritis in dairy cows. A total number of fourteen postpartum clinical endometritic cows selected after screening were allotted randomly into 2 equal groups (n=7). The Group I & II cows were intrauterinely administered with ozone insufflations either alone or in combination with cephalexin (Lixen-IU®). Seven postpartum normal cyclic animals were taken as control. Following treatment the overall reduction in combined mucous character and odour both in group I (82.04%) and group II (87.25%) were similar and highly significant (p<0.01). The most predominant bacteria found was E. coli (28.57%) followed by Pseudomonas spp. (14.28%), Staphylococcus spp. (21.42%), Streptococcus spp. (21.42%), Proteus spp. (7.14%) and Acinetobacter calcoaceticus (7.14%). Overall reduction in bacterial count on pre (day 1) and post treatment (day 7) were highly significant (p<0.01) i.e. 99.60% in group I and 99.72% group II. PMN cell counts of uterine smear were significantly (p<0.01) increased from pre treatment (25.85±3.28 in group I and 22.85±2.77) in group II) to post treatment (77.71±2.86) in group I and 87.14±1.35 in group II) which indicated the infiltration of neutrophils due to action of ozone and cephalexin. The conception rates following first AI were recorded as 42.85% in group I (3/7) and 71.42% (5/7) in group II. Thus intrauterine ozone insufflation has the potential to alleviate postpartum clinical endometritis as an efficacious, cost effective treatment option and an alternative to antibiotics with an overall improvement of fertility rate in dairy cows.